2019
DOI: 10.1080/00207233.2019.1695445
|View full text |Cite
|
Sign up to set email alerts
|

Testing the environmental Kuznets curve hypothesis: an empirical study for East African countries

Abstract: The green economy aims to achieve economic growth and development without an adverse effect on the environment. The environmental Kuznets curve (EKC) hypothesis explains the relationship between economic activity and environmental degradation. Using the EKC hypothesis as a theoretical framework, this study tested the EKC hypothesis for 12 East African countries using the Pooled Mean Group (PMG) approach for the period from 1990 to 2013. The result shows that the relationship between per capita income and CO 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(58 citation statements)
references
References 66 publications
1
42
0
Order By: Relevance
“…Achieving sustainable economic growth without any adverse effect on the natural environment is crucial these days. Demissew Beyene and Kotosz [45] shows that the long-run association between the economic growth and CO 2 emission is not as Kuznets assumed (an inverted-shape), but instead of bell-shaped which means that the relationship between GDP per capita and CO 2 emission is negative until the GDP per capita reaches to a certain point and once it reaches to a certain point the relationship between the stated variable is positive. The study conducted in the USA for the period of 1960-2013 by Dogan and Turkekul [46] to investigate the relationship between CO 2 emissions energy consumption, real output the square of real output, trade openness, urbanization, and financial development by using ARDL bound testing approach and Vector Error Correction Model (VECM) revealed that the main source of CO 2 emission is energy consumption in the USA and urbanization also has a positive impact on CO 2 emission.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Achieving sustainable economic growth without any adverse effect on the natural environment is crucial these days. Demissew Beyene and Kotosz [45] shows that the long-run association between the economic growth and CO 2 emission is not as Kuznets assumed (an inverted-shape), but instead of bell-shaped which means that the relationship between GDP per capita and CO 2 emission is negative until the GDP per capita reaches to a certain point and once it reaches to a certain point the relationship between the stated variable is positive. The study conducted in the USA for the period of 1960-2013 by Dogan and Turkekul [46] to investigate the relationship between CO 2 emissions energy consumption, real output the square of real output, trade openness, urbanization, and financial development by using ARDL bound testing approach and Vector Error Correction Model (VECM) revealed that the main source of CO 2 emission is energy consumption in the USA and urbanization also has a positive impact on CO 2 emission.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This implies that the amount of heat trapped in the atmosphere is in the upward trend. In the case of Sub-Saharan Africa, for instance, Demissew Beyene and Kotosz (2019) noted that carbon dioxide emissions have reached their peak between the year 1990 and 2014 (precisely in 2003). However, the study expressed that a decline in carbon emissions was experienced in Sub-Saharan Africa between 2007 and 2013 before starting to increase again in the year 2014.…”
Section: Introductionmentioning
confidence: 99%
“…References [33][34][35] [37,38]. Reference [39] has used PMG approach for 12 East African countries for the period from 1990 to 2013 and reported a U-shaped long-run relationship between per capita income and CO 2 emissions. Finally, using data from 31 developing countries and applying dynamic panel threshold framework, no evidence can be provided to support either the EKC hypothesis or causal relationship between CO 2 emission and economic growth [40].…”
Section: Studies That Do Not Support the Ekc Hypothesismentioning
confidence: 99%
“…Due to its numerous attractive features over the other alternative models, our study applies the recently developed PMG/ARDL approach, which is becoming increasingly popular in the empirical research. PMG estimation approach assumes that the parameters are heterogeneous across groups [39]. The PMG estimator combines pooling and averaging of coefficients.…”
Section: Model Specificationmentioning
confidence: 99%